Neutron Halo Structure of Unstable Exotic 14B and 18N Nuclei - Hamad, Moath S.; Abdullah, Ahmed N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The ground-state properties like the nuclear densities and the root mean square (rms) radii for exotic neutron-rich nuclei 14B and 18N have been investigated using the Skyrme Hartree-Fock and Bear-Hodgson calculations to study the structure of these nuclei. The results of the evaluation are contrasted with the experimental data that is currently available. It found that a common feature of the neutron and matter densities for the above-selected exotic nuclei is the long tail behavior. We assumed that both 14B and 18N have a structure of the core nuclei 13B and 17N plus a valence neutron. It found that the structure of the valence one-neutron of 14B and 18N is a pure Configuration. The elastic charge form factors of the above selected exotic nuclei are evaluated using the plane wave Born approximation and compared with those of their stable isotope 10B and 14N